Case study: Blackbonzr / Nur Aiman Nadiah Abdul Rahaman ... [et al.] - Abdul Rahaman, Nur Aiman Nadiah; Razali, Ahmad Daniel; Mohammed, Nurul Asyikin; Che Kar, Nur Atirah (2021)
Mr. Hisyam is a supplier of watches and accessories in Blackbonzr company from 2016 till now. His vision and mission in marketing watches are to put the customers first and make sure that his customers are satisfied with his product and services. He also set a goal to provide excellent watches and accessories as the best local market supplier in Malaysia. Mr. Hisyam has a flexible part-time home business to make extra income by being a supplier of watchers and accessories. As a supplier, he owns a business without the hassle of handling products and services. After receiving payment from a customer, the company will pay him as a supplier. He will then send the product to the customer under his business name. He also does not need stock, and he no needs to store, receive, or send out supplies, as his company does all that for him. However, he needs to face a few things, including competing in a similar product and lack of quality control. As a supplier, he cannot personally check the watch quality because the company will send the product directly to his customer. As a supplier of watcher industry, he creates e-market platforms, variation of payment methods, and provide exceptional services as his marketing and management strategies. He uses Facebook, Instagram, Whatsapp, and Telegram as his digital marketing platform as they are fast go-to-market time, low cost, and content marketing strategy. Besides, it will provide more information for customer decision-making, customer data insights, and convenience to buy goods or services without causing any physical constraints to the consumers due to bad weather. He applies online and cash payment methods and provides packing, promoting, and delivering watch and accessories services. Therefore, he invested RM 250 to a start-up capital investment as his financial resource to sign as a watch supplier in 2016. Having a capital investment, will increase the operational capacity, capture a larger share of the market, and generate more revenue than drop shipping. His watch value propositions are more affordable, friendly services, convenient to use as they are waterproof watches, and provide couple watches set. He also promotes discounts, gift features, and watch warranty cover to achieve customer loyalty and satisfaction.